Sintering effect on mechanical properties of composites of hydroxyapatite lanthanum oxide (HA-La2O3) - (:unkn) unknown (Trans Tech Publications Ltd, 2006)
Composites of calcinated bovine bone derived hydroxyapatite (HA) with 0.25, 0.5, 1, and 2 wt % La2O3 were prepared by sintering. The experimental results indicated that compression strength and microhardness of HA-La2O3 composites increase when the content of La 2O3 and sintering temperature increase. The best mechanical properties were achieved after sintering at 1300°C. The results are in agreement with densification measurements and microstructure analysis.
Keywords: Hydroxyapatite; Lanthanum Oxide; Mechanical Properties; Sintering